Nickel‐Catalyzed α‐Allylation of Aldehydes and Tandem Aldol Condensation/Allylation Reaction with Allylic Alcohols. Issue 26 (29th May 2017) - Bernhard, Yann; Thomson, Brodie; Ferey, Vincent; Sauthier, Mathieu
Abstract: An additive‐free nickel‐catalyzed α‐allylation of aldehydes with allyl alcohol is reported. The reaction is promoted by 1 mol % of in situ formed nickel complex in methanol, and water is the sole by‐product of the reaction. The experimental conditions allow the conversion of various α‐branched aldehydes and α, β‐unsaturated aldehydes as nucleophiles. The same catalyst and reaction conditions enabled a tandem aldol condensation of aldehyde/α‐allylation reaction. Abstract : Nickel‐based catalysts efficiently promote the α‐allylation of α‐branched aldehydes and α, β‐unsaturated aldehydes with allylic alcohols under additive‐free conditions. The reaction proceeds with high yield and water is formed as the only byproduct. The nickel catalysts proved to be suitable for the promotion of a tandem aldolisation/allylation reaction of simple linear aldehydes with allylic alcohols.